Gender, status, & tax offenses over time - Reese, Bruce (Deviant behavior, 2021)
Men are more likely than women to commit tax offenses, and previous research has suggested that this difference can be partially explained by status processes. This study investigates whether the relationship between status and tax offenses has changed over time in synchrony with changes in social stratification based on gender, race, and class. We hypothesize that if gender equality has increased within U.S. society (particularly within the formal economy), then gender-based discrepancies in tax offending should have decreased as well. Using administrative data from federal criminal cases sentenced between 1995-2015, we examine how the effects of different indicators of status - including race, class, and gender - on the odds of being convicted for a tax offense have changed over time. Results from a series of logistic regression models indicate that over time the difference in the probability of men and women being convicted of a tax offense versus another white collar crime decreases. Other variables of status including race, age, and education are also analyzed and discussed.